2011
DOI: 10.1103/physrevlett.107.187204
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NMR Relaxation of Tomonaga-Luttinger Liquids and the Magnitude of the Carbon Hyperfine Coupling in Single-Wall Carbon Nanotubes

Abstract: Recent transport measurements [Churchill et al. Nature Phys. 5, 321 (2009)] found a surprisingly large, 2-3 orders of magnitude larger than usual 13 C hyperfine coupling (HFC) in 13 C enriched single-wall carbon nanotubes. We formulate the theory of the nuclear relaxation time in the framework of the Tomonaga-Luttinger liquid theory to enable the determination of the HFC from recent data by Ihara et al.[Europhys. Lett. 90, 17 004 (2010)]. Though we find that 1=T 1 is orders of magnitude enhanced with respect t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Partly motivated by these attractive features, a series of experiments was carried out with clean CNTs, aiming to control and measure the spin and valley degrees of freedom of electrons confined in QDs [16,17,21,22]. Surprisingly, two of these experiments using 13 C-enriched samples revealed effects compatible with an atomic HF strength that is two orders of magnitude larger than theoretically calculated [9,23] and measured via nuclear magnetic resonance [24,25]. The resolution of this discrepancy is an open problem [2], bearing strong relevance for HF-related phenomena in CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Partly motivated by these attractive features, a series of experiments was carried out with clean CNTs, aiming to control and measure the spin and valley degrees of freedom of electrons confined in QDs [16,17,21,22]. Surprisingly, two of these experiments using 13 C-enriched samples revealed effects compatible with an atomic HF strength that is two orders of magnitude larger than theoretically calculated [9,23] and measured via nuclear magnetic resonance [24,25]. The resolution of this discrepancy is an open problem [2], bearing strong relevance for HF-related phenomena in CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kiss et al demonstrated that the magnitude and temperature dependence of (T 1 T ) −1 reported by Ihara et al can be explained quantitatively in the framework of TLL theory. 26,37 They found that the NMR relaxation rate is enhanced by orders of magnitude compared to a Fermi liquid with the same density of states (DOS) due to a TLL state. 37 They derived the equation…”
Section: Resultsmentioning
confidence: 99%
“…26,37 They found that the NMR relaxation rate is enhanced by orders of magnitude compared to a Fermi liquid with the same density of states (DOS) due to a TLL state. 37 They derived the equation…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the theoretical works addressing few-electron physics in CNT DQDs [29,[42][43][44][45][46][47][48][49], Refs. [43,49] described the Pauli blockade transport effect in the case of a straight CNT.…”
Section: Magnetic Anisotropy Of the Leakage Currentmentioning
confidence: 99%